Interdisciplinary treatment of hypodontia of upper lateral incisors in adult patients – systematic review of literature - Rafałowicz, Barbara; Wagner, Leopold (Journal of Stomatology, 2017)
Introduction. Hypodontia is malformation of dentition characterized by deficit of one to six tooth germs. Hypodontia of upper lateral incisors occurs in 27% of cases and is ranked second with regard to incidence. Etiology of hypodontia is complex and results from interaction of various factors in the process of formation and development of tooth germs. Hypodontia of upper lateral incisors may be genetically, phylogenetically, neurogenically, environmentally conditioned, or may result from premature ossification of sella turcica. Complex etiology of hypodontia is reflected in complex treatment protocols of this condition. Aim of the study. To perform systematic literature review of therapeutic procedures regarding hypodontia of upper lateral incisors in adults. Material and methods. The data were collected with the use of Medline, PubMed, Cochrane Library and available library resources. The search terms were: hypodontia, interdisciplinary, orthodontic and prosthetic treatment of hypodontia, canine mesialization, implant, mini implant and fixed prosthesis. Conclusion. On the basis of obtained information it must be stated that rehabilitation of adult patients with diagnosed hypodontia of upper lateral incisors is a difficult clinical procedure. Therapeutic procedures are complex and require interdisciplinary approach, which takes into account dentition, patients’ preferences, age as well as type of future prosthetic restoration. Treating patients